2009
DOI: 10.1103/physrevb.80.165334
|View full text |Cite
|
Sign up to set email alerts
|

Role of segregation in InAs/GaAs quantum dot structures capped with a GaAsSb strain-reduction layer

Abstract: Please check the document version of this publication:• A submitted manuscript is the version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 87 publications
(80 reference statements)
4
44
0
1
Order By: Relevance
“…34 . Along these same lines Haxha et al 35 reported that intermixing of 3 atomic layers was needed to achieve good agreement with experimental results. This is not in contradiction with the results we present below since the model presented by Haxha et al is a mean field model and in order to describe the intermixing captured by our KMC model it was necessary to explicitly include exchange between surface and subsurface atoms.…”
Section: Methodsmentioning
confidence: 64%
“…34 . Along these same lines Haxha et al 35 reported that intermixing of 3 atomic layers was needed to achieve good agreement with experimental results. This is not in contradiction with the results we present below since the model presented by Haxha et al is a mean field model and in order to describe the intermixing captured by our KMC model it was necessary to explicitly include exchange between surface and subsurface atoms.…”
Section: Methodsmentioning
confidence: 64%
“…The most common capping materials used for the reduction of strain inside dots are InGaAs (Dasika et al, 2009;Kim et al, 2003) and GaAsSb (Haxha et al, 2009;Bozkhurt et al, 2011;Ulloa et al, 2007;Akahane et al, 2004), sometimes InAlAs or some combination of these materials is used (Liu et al, 2005;Kong et al,2008). Strain reducing layers covering InAs dots are used to shift the emission wavelength to 1.3 µm and 1.55 µm, typical of optical fibre communication.…”
Section: Strain Reducing Capping Layersmentioning
confidence: 99%
“…To be embedded in a functional structure, dots must be covered by a capping layer. Capping of quantum dots is currently a very important topic of research (Bozkhurt et al, 2011;Dasika et al, 2009;Haxha et al, 2009;Kong et al, 2008). The overgrowth process is essential to obtain dot parameters necessary for the realization of novel optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the difficulty of incorporating Sb on GaAs has been repeatedly reported in the literature [15]. Indeed, the effect of interdiffusion, which affects the relative composition of In/Ga and As/Sb in and around the QDs, is still debated [16,17]. An alternative approach to control the Sb distribution is the use of postgrowth thermal annealing that can be used to tailor the band alignment, the wave function overlaps, and hence the recombination dynamics in the InAs/GaAsSb type II QDs [18].…”
Section: Introductionmentioning
confidence: 99%